Periodicity in Structure, Bonding, and Reactivity for p‐Block Complexes of a Geometry Constraining Triamide Ligand. Issue 71 (26th November 2019) - Marczenko, Katherine M.; Zurakowski, Joseph A.; Kindervater, Marcus B.; Jee, Samantha; Hynes, Toren; Roberts, Nicholas; Park, Seoyeon; Werner‐Zwanziger, Ulrike; Lumsden, Michael; Langelaan, David N.; Chitnis, Saurabh S.
Abstract: The use of pincer ligands to access non‐VSEPR geometries at main‐group centers is an emerging strategy for eliciting new stoichiometric and catalytic reactivity. As part of this effort, several different tridentate trianionic substituents have to date been employed at a range of different central elements, providing a patchwork dataset that precludes rigorous structure–function correlation. An analysis of periodic trends in structure (solid, solution, and computation), bonding, and reactivity based on systematic variation of the central element (P, As, Sb, or Bi) with retention of a single tridentate triamide substituent is reported herein. In this homologous series, the central element can adopt either a bent or planar geometry. The tendency to adopt planar geometries increases descending the group with the phosphorus triamide (1 ) and its arsenic congener (2 ) exhibiting bent conformations, and the antimony (3 ) and bismuth (4 ) analogues exhibiting a predominantly planar structure in solution. This trend has been rationalized using an energy decomposition analysis. A rare phase‐dependent dynamic covalent dimerization was observed for 3 and the associated thermodynamic parameters were established quantitatively. Planar geometries were found to engender lower LUMO energies and smaller band gaps than bent ones, resulting in different reactivity patterns. These results provide a benchmark dataset to guide further research in this rapidly emerging area. Abstract : A longitudinal study of strained p‐block triamides : A comprehensive analysis of periodic trends in structure, bonding, and reactivity for geometry constrained triamide complexes of P, As, Sb, and Bi is reported. In this homologous series, the central element can adopt either a bent or planar geometry and the preferred orientation in the solid and solution phases (as well as computationally) have been mapped. Additionally, the influence of geometry on reactivity has been elucidated.